The Number Of Family Caregivers Helping Older US Adults Increased From 18 Million To 24 Million, 2011-22 - Wolff, Jennifer L; Cornman, Jennifer C; Freedman, Vicki A (Health affairs (Millwood, Va.), 2025)
The evolving composition and experiences of the family caregiver workforce have profound ramifications for public policy but are not well understood. Drawing on the linked National Health and Aging Trends Study and National Study of Caregiving, we found that the numbers of family caregivers providing help to older adults increased by nearly six million between 2011 and 2022, rising from 18.2 million to 24.1 million. Among older adults receiving care, network size was stable, at about two caregivers per older adult at both points in time. However, in 2022, family caregivers were assisting older adults who were younger, more likely to be male and better educated, and less likely to have dementia. We found few changes in competing work and child care responsibilities, weekly care hours, and caregiving-related difficulty. A smaller number of family caregivers were assisting fewer older adults with dementia, but in this group, co-residence increased by 25 percent, average care hours increased by 50 percent, and employment decreased. For family caregivers as a whole, challenges persist, and for those assisting people with dementia, tailored surveillance and effective support programs are needed.